The Relationship Between Forward Head Posture with Hand Grip Strength and Thoracic Kyphosis Among Young Adults - Akkaş, Yunis; Acar, Ahmet Gökhan; Alsancak, Serap; Güner, Senem (The European Research Journal, 2026)
Objective: Forward head posture (FHP) is a common postural abnormality where the external auditory canal is positioned ahead of the shoulder joint’s plumb line. This study aimed to evaluate FHP’s impact on thoracic kyphosis, hand grip strength, and pinch grip strength in healthy adults. Methods: Ninety-three healthy adults (18–25 years) participated, divided into two groups based on craniovertebral angle (CVA): the FHP group (CVA <45°, n=38) and the control group (CVA >45°, n=55). CVA was measured via photogrammetry. The thoracic kyphosis angle was assessed using the Goniometer Pro app. Hand grip strength was measured with a Jamar dynamometer, and pinch grip strength with a Baseline hydraulic pinch gauge. Results: No significant differences were found between groups in thoracic kyphosis angle, hand grip, or pinch grip strength (P>0.05). CVA showed no significant correlation with these parameters in either group (P>0.05). However, in the FHP group, the thoracic kyphosis angle was significantly correlated with non-dominant hand grip strength (r= -0.324, P=0.047), dominant pinch grip strength (r= -0.350, P=0.031), and non-dominant pinch grip strength (r= -0.394, P=0.014). Conclusion: Hand grip and pinch grip strength were not affected by FHP in asymptomatic young adults. No relationship was found between CVA and thoracic kyphosis. However, individuals with FHP and thoracic kyphosis angles above 40° may experience altered non-dominant hand function, potentially due to kyphotic changes.